2016
DOI: 10.18203/2320-6012.ijrms20160541
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of surgical management of tibial plateau fractures in adults

Abstract: INTRODUCTIONTibial plateau fractures occur when proximal tibia experiences an excessive axial load. The mechanism of injury and the energy required to cause these fractures are age dependent. Younger patients tend to sustain these fractures secondary to high energy trauma such as fall from height and motor vehicle accidents, while older patients sustain tibial plateau fractures secondary to low energy trauma such as low level fall or stumble.The management of these types of injuries has for long been subject o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In these 3 weeks, the patient was made to stand up supported and walk with the help of walker. 23,24 Patients who did not adhere to these essential post-operative rehabilitation protocols had a decreased range of knee flexion and 2 patients also developed knee stiffness. This is a short term study to assess the functional outcome of tibial plateau fracture plating done in a small number of patients within the same demographic area.…”
Section: Discussionmentioning
confidence: 99%
“…In these 3 weeks, the patient was made to stand up supported and walk with the help of walker. 23,24 Patients who did not adhere to these essential post-operative rehabilitation protocols had a decreased range of knee flexion and 2 patients also developed knee stiffness. This is a short term study to assess the functional outcome of tibial plateau fracture plating done in a small number of patients within the same demographic area.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by the Kehribar and Karapinar (2019) observed that 29(87.9%) were males and three (12.1%) were females. A study conducted by the Swarup et al (2016) observed that out of 60 study participant, 78% were males & 22% were females. A study conducted by the Jakinapally et al (2018) observed that out of 20 study participants, 15 (75%) were males and ive (25%) were females.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by the Swarup et al (2016) observed that out of 60 study participants inal end result as per Rasmussen's criteria was excellent in 37, good in 11, fair in six and poor in six patients. A study conducted by the Jakinapally et al (2018) observed that nine (45%), cases had excellent outcome, seven (35%) cases had a good outcome, three (15%) cases had fair outcome and one (5%) case had a poor outcome.…”
Section: Figure 4: Xray Images Of a Case Of Tibial Plateau Managed Wimentioning
confidence: 99%
See 2 more Smart Citations